Fish Paralog Proteins RNASEK-a and -b Enhance Type I Interferon Secretion and Promote Apoptosis - Sun, Zhi-Chao; Jiang, Zeyin; Xu, Xiaowen; Li, Meifeng; Zeng, Qing; Zhu, Ying; Wang, Shanghong; Li, Yuanyuan; Tian, Xiao-Li; Hu, Chengyu (Frontiers in Immunology, 2021)
Type Ι interferon and apoptosis elicit multifaceted effects on host defense and various diseases, such as viral infections and cancers. However, the gene/protein network regulating type Ι interferon and apoptosis has not been elucidated completely. In this study, we selected grass carp (Ctenopharyngodon idella) as an experimental model to investigate the modulation of RNASEK on the secretion of type Ι interferon and apoptosis. We first cloned two paralogs RNASEK-a and -b in grass carp, defined three exons in each gene, and found the length of both coding regions is 306 bp with 73.27% of protein homology. The protein sequences of two paralogs are highly conserved across species. Two proteins were mainly localized in early and late endosomes and endoplasmic reticulum. Further, quantitative real-time PCR demonstrated dsRNA poly I:C and grass carp reovirus up-regulated RNASEK-a and -b in grass carp cells and tissues. Overexpression of RNASEK-a and -b individually induced type Ι interferon expression and the phosphorylation of IRF3/IRF7 shown by western blot and immunofluorescent staining, increased Bax/Bcl-2 mRNA ratio, DNA fragmentations, TUNEL-positive cells, and proportion of Annexin Ⅴ-positive signals in flow cytometry, and activated eIF2α, opposite to that observed when RNASEK-a and -b were knocked down in multiple cell types. Taken together, we claim for the first time that fish paralog proteins RNASEK-a and -b enhance type Ι interferon secretion and promote apoptosis, which may be involved in the phosphorylation of IRF3/IRF7 and eIF2α, respectively. Our study reveals a previously unrecognized role of RNASEK as a new positive regulator of type Ι interferon and apoptosis.